THE EFFECT OF RISK GOVERNANCE ON BANK PERFORMANCE: EVIDENCE FROM INDONESIAN BANKS - Selty Tan; Hesniati Hesniati; Serly Serly (Universitas Nusa Cendana, 2026)
This study investigates the impact of risk governance on banking performance in Indonesia using a quantitative approach. Panel data regression is applied to 235 bank-year observations from 47 commercial banks over the 2018–2022 period, with the sample selected through purposive sampling based on data availability and governance disclosures. Bank performance is measured using Return on Assets (ROA) and Return on Equity (ROE), while risk governance is proxied by the Risk Governance Index (RGOV), constructed from risk governance disclosures in annual reports. The empirical findings demonstrate that risk governance has a positive and statistically significant effect on both ROA and ROE, thereby supporting the proposed hypotheses. These results indicate that banks with stronger risk governance frameworks tend to achieve more efficient asset utilization and generate higher returns for shareholders, even after controlling for bank-specific characteristics and time effects. This evidence underscores the importance of robust risk oversight mechanisms in enhancing managerial discipline and operational effectiveness. The study contributes to the corporate governance literature by providing empirical evidence from an emerging market context, particularly within the Indonesian banking sector. From a practical standpoint, the findings suggest that bank management and regulators such as Otoritas Jasa Keuangan and Bank Indonesia should prioritize the strengthening of risk governance structures to promote sustainable performance, financial stability, and long-term resilience in banking institutions. Keywords: Risk Governance Index; Bank Performance; Agency Theory